Analysis of Behavioral Strategies of Construction Safety Subjects Based on the Evolutionary Game Theory - Wu, Fan; Xu, Haiying; Sun, Kuo-Shun; Hsu, Wei-Ling (Buildings (Basel), 2022)
In construction safety management practices, identifying key stakeholders and specifying their safety behavior patterns are critical to avoid unsafe practices, which are the major cause of construction accidents. This paper argues that the main contractor and construction workers are key safety stakeholders in the construction safety management in China. The purpose of this paper is to develop an evolutionary game model to explore the safety behavior strategies of the main contractor and construction workers. In this framework, we explored the effects of model parameter changes on the evolution of safety behavior strategies and verify the evolution paths under different initial values by numerical simulations. The findings of this paper are as follows: Firstly, the safety and stability of construction projects are related to the possible losses caused by accidents, the amount of work required by construction workers to comply with safety regulations, the gain of bravado, the probability of accidents, and cost savings from the main contractor’s lax supervision. Secondly, the role of restraining the unsafe behavior of construction workers through the form of fines is limited, and increasing the fines to the main contractor cannot effectively reduce the unsafe behaviors. Thirdly, strengthening safety education, creating a safe atmosphere, and optimizing operating procedures are effective measures to improve the effectiveness of safety behavior. This study further extends the application of evolutionary game theory to construction safety management, and the findings can provide clear guidance for the development of effective incentives and constraints on safety behavior.